Preparation method of self-supporting thin film hard carbon material
Through the preparation method of self-supporting thin film hard carbon materials, the problems of few active sites and poor sodium storage performance of pure carbon materials are solved, and the performance of efficient sodium ion batteries is improved significantly, and the capacity retention rate and Coulomb efficiency are significantly improved.
Patent Information
- Application Number
- CN202411352827.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, pure carbon materials have fewer electrode negative active sites, poor sodium storage performance, and poor circulation stability of the material, which cannot meet the actual use needs.
By using the preparation method of self-supporting film hard carbon material, polyamic acid is formed by in situ polymerization of para-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic acid dianhydride in N-methylpyrrolidone, through sub- Amination and carbonization treatment form pore-rich hard carbon materials, increasing active sites and cycling stability.
The sodium storage and circulation performance of the material are improved. After 200 cycles at a current density of 50 mA g-1, the capacity retention rate is 90%~96%, and the first Coulomb efficiency is 60%~90%.
Smart Images

Figure CN119191844A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal ion battery negative electrode material development and relates to a method for preparing a self-supporting thin film hard carbon material. Background Art
[0002] With the depletion of fossil energy and the increasing environmental problems caused by the excessive use of fossil energy, the rapid development of science and technology and economic construction has an urgent need for renewable clean energy. The development of human society is inseparable from the acquisition, storage and conversion of energy, so the research and development of new environmentally friendly energy and large-scale energy storage devices has been continuously developed. Because of its abundant reserves, low cost and similar physical and chemical properties to lithium, sodium-ion batteries are expected to complement lithium-ion batteries in the fields of large-scale electrochemical energy storage and low-speed electric vehicles. Among them, anode materials are one of the important components of electrode materials required to construct sodium-ion batteries. Carbon-based materials may eventually become the future commercial sodium-ion battery anode materials due to their low cost, abundant resources and environmental friendliness. With the strong demand for electric vehicles, portable electronic products and wearable devices, the development of flexible carbonaceous negative electrode materials with high mechanical strength, high energy density and excellent comprehensive sodium storage performance has become one of the key research directions of academia and industry.
[0003] Researchers synthesized carbon materials from different precursors and heat-treated them under different conditions to obtain negative electrode carbon materials with better electrochemical performance. However, due to the small number of active sites in the negative electrode carbon materials, the sodium storage performance is poor, and the material's cycle stability is poor, it cannot meet the needs of actual use. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a self-supporting thin film hard carbon material, thereby solving the technical problems in the prior art that the pure carbon material has fewer negative electrode active sites, poor sodium storage performance, and poor cyclic stability of the material.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a self-supporting thin film hard carbon material comprises the following steps: S1: dissolving p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride in N-methylpyrrolidone, and performing in-situ polymerization to obtain a polyamic acid solution; S2: preparing a polyamic acid film using the polyamic acid solution, wherein the thickness of the polyamic acid film is in the micrometer level; S3: performing imidization treatment on the polyamic acid film to obtain a polyimide film; S4: Under an argon atmosphere, the polyimide film is carbonized to obtain the self-supporting film hard carbon material. During the carbonization, a pressure of 80-480 Pa is applied to the polyimide film.
[0006] Preferably, in step S1, p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride are dissolved in N-methylpyrrolidone, specifically: p-phenylenediamine is dissolved in N-methylpyrrolidone, and after ultrasonic treatment, 3,3',4,4'-biphenyltetracarboxylic dianhydride is added in batches, and stirred evenly to obtain the polyamic acid solution; the ratio of the p-phenylenediamine to the N-methylpyrrolidone is 1 mol: (35~60) mL.
[0007] Preferably, in step S1, the molar ratio of the p-phenylenediamine to the 3,3',4,4'-biphenyltetracarboxylic dianhydride is (1-1.02):1.
[0008] Preferably, in step S2, the thickness of the polyamic acid film is 10-20 μm.
[0009] Preferably, in step S3, the imidization treatment is specifically: performing a gradient temperature treatment within a range of 100 to 350° C., and the treatment time at each temperature is 0.5 to 1 h.
[0010] Preferably, during the gradient temperature increase treatment, the temperature increase rate is 2-5°C / min.
[0011] Preferably, in step S4, the temperature of the carbonization treatment is 700-1300° C., and the time is 1-2 hours.
[0012] A self-supporting thin film hard carbon material is prepared by the above method.
[0013] A negative electrode material comprises the above-mentioned self-supporting thin film hard carbon material.
[0014] A sodium ion battery, comprising the above-mentioned negative electrode material, wherein the sodium ion battery has an output current of 50 mA g -1 After 200 cycles at a current density of 1.547 W, the capacity retention rate is 90%~96%, and the first coulombic efficiency is 60%~90%.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a self-supporting thin film hard carbon material. First, the method selects p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride as raw materials. The two compounds are polymerized in situ in N-methylpyrrolidone to form polyamic acid. The molecular structures of the two raw materials have a rigid molecular structure and a strong covalent bond, and the polyimide exhibits extremely high thermal stability and good mechanical properties; and the polyimide synthesized from the two monomers has more oxygen-containing functional groups, and the oxygen-containing functional groups (such as hydroxyl, carboxyl, carbonyl and ether groups, etc.) can increase the surface activity of the carbon material. After high-temperature carbonization, defects are formed, and the material is also rich in pores, generating a large number of active sites, thereby improving its affinity with the electrolyte. In addition, in the preparation process of the polyamic acid film, by controlling the thickness of the film at the micron level, it is helpful to form a uniform and dense film structure. This structure can maintain good morphological stability in the subsequent carbonization process, forming a self-supporting structure, and no other supporting materials are required when in use. In addition, the process is also conducive to the uniform distribution of active sites. Furthermore, the polyamic acid film is transformed into a polyimide film through imidization treatment, so that the amide groups in the polyamic acid molecules are converted into more stable imide groups. This process effectively increases the number of active sites in the film. Finally, carbonization treatment under argon atmosphere is a key step in the preparation of hard carbon materials. Argon, as an inert gas, can protect the film from oxidation during the carbonization process, thereby maintaining its original chemical structure. At the same time, the pressure of 80~480Pa applied during the carbonization process helps promote the chemical transformation and rearrangement inside the film, which increases the number of defects in the material, effectively increases the number of active sites, improves the sodium storage performance of the material, and enhances the material's cycle performance.
[0016] Furthermore, another inventive point of the present invention is that in step S1, p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride are dissolved in N-methylpyrrolidone, specifically: p-phenylenediamine is dissolved in N-methylpyrrolidone, and after ultrasonic treatment, 3,3',4,4'-biphenyltetracarboxylic dianhydride is added in batches, and stirred evenly to obtain the polyamic acid solution; the ratio of p-phenylenediamine to N-methylpyrrolidone is 1 mol: (35~60) mL. First, ultrasonic treatment can enhance the dissolution effect of p-phenylenediamine in NMP, so that the p-phenylenediamine molecules are more evenly dispersed in the solvent to form a stable solution. Adding 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches can effectively control the reaction rate and reaction degree, and adding in batches can make the reaction proceed smoothly, which is conducive to the production of high-quality polyamic acid. The ratio of p-phenylenediamine to NMP is 1 mol: (35~60) mL, which helps to form a stable solution system. Too much NMP will dilute the concentration of the reactants and reduce the reaction rate; while too little NMP may not be able to fully dissolve p-phenylenediamine, resulting in an uneven reaction.
[0017] Furthermore, another inventive point of the present invention is that in step S1, the molar ratio of the p-phenylenediamine to the 3,3',4,4'-biphenyltetracarboxylic dianhydride is (1~1.02):1. First, a slight excess of p-phenylenediamine can ensure the complete reaction of 3,3',4,4'-biphenyltetracarboxylic dianhydride. Secondly, the precise control of the molar ratio helps to generate polyamic acid (PAA) with specific structure and performance. The molecular structure of PAA directly affects the subsequent preparation of polyimide (PI) film and the performance of the final hard carbon material. The appropriate molar ratio can ensure the uniformity and integrity of the PAA molecular chain, thereby improving the quality and stability of the final product. When the reactants are completely converted, the amount of by-products generated will be reduced accordingly. The by-products will not only reduce the purity of the product, but may also have an adverse effect on the subsequent processing steps. By controlling the excess of p-phenylenediamine within a smaller range (1~1.02 times), the generation of by-products can be minimized while ensuring the completeness of the reaction.
[0018] Further, another inventive point of the present invention is that in step S2, the thickness of the polyamic acid film is 10-20 μm, and the thinner film thickness helps to achieve the uniformity of the film. During the preparation process, the thinner film is easier to control its thickness distribution and reduce the uneven thickness, which is crucial for the subsequent processing steps (such as imidization and carbonization) and the performance of the final product. Within this thickness range, the polyamic acid film can maintain good mechanical properties, such as flexibility, tensile strength, etc., which are very important for the self-support of the film and the stability in the subsequent processing process. The polyamic acid film needs to withstand high temperature treatment during the subsequent imidization and carbonization process, and the thinner film thickness helps to transfer and disperse heat faster, thereby improving the thermal stability of the film. In addition, the thinner film is also more likely to form a porous structure during the carbonization process, which helps to further improve the thermal stability and number of active sites of the material. The thickness of the film directly affects the ratio of its surface area to volume. At the same volume, the thinner film has a larger surface area, so that more active sites can be exposed, which is of great significance for improving the electrochemical properties and adsorption properties of the material.
[0019] Furthermore, another inventive point of the present invention is that in step S3, the imidization treatment is specifically: a gradient temperature rise treatment is performed within 100-350°C, and the treatment time at each temperature is 0.5-1h. The gradient temperature rise treatment can gradually adapt the PAA film to the temperature change and avoid the stress concentration phenomenon caused by the sudden temperature rise, which helps to reduce the deformation and cracking of the film during the imidization process and maintain the integrity and flatness of the film. By gradually performing the imidization reaction at different temperatures, it can be ensured that the reaction is carried out uniformly inside the film. The lower temperature first triggers a partial imidization reaction. As the temperature rises, the reaction gradually deepens and is complete. This step-by-step approach helps to form a uniform polyimide (PI) structure.
[0020] Furthermore, another inventive point of the present invention is that during the gradient heating process, the heating rate is 2~5℃ / min, and the heating rate directly affects the kinetic process of the imidization reaction. The slower heating rate (2~5℃ / min) allows the reaction system to have enough time to reach thermal equilibrium at each temperature point, thereby ensuring that the reaction is carried out under controllable conditions, which helps to reduce side reactions or structural defects caused by temperature mutations. The slower heating rate helps to reduce the thermal stress generated in the film during the heating process. When the temperature rises too quickly, the temperature gradient inside the film is large, which may lead to thermal stress concentration, thereby causing deformation or cracking of the film, while the slower heating rate can gradually adapt the film to temperature changes and reduce the generation of thermal stress. The slow heating process allows the reactant molecules to have enough time to diffuse and rearrange inside the film, thereby ensuring that the imidization reaction is carried out uniformly inside the film, which helps to form a uniform PI structure and improve the overall performance of the film.
[0021] Further, another inventive point of the present invention is that in step S4, the temperature of the carbonization treatment is 700~1300℃, and the time is 1~2h. Carrying out the carbonization treatment within this temperature range can ensure that the organic components in the PI film are fully decomposed and converted into carbon. As the temperature increases, the non-carbon elements (such as oxygen, nitrogen, hydrogen, etc.) in the PI molecular chain are gradually removed to form a more stable carbon structure, which usually has high thermal stability and chemical stability. The carbonization temperature and time have an important influence on the pore structure of the final carbon material. At the appropriate temperature and time, the carbonization process can form rich micropores and mesopore structures. These pore structures help to increase the specific surface area and the number of active sites of the material, thereby improving its electrochemical properties, adsorption properties, etc. As the carbonization temperature increases, the degree of graphitization in the carbon material gradually increases, and the conductivity is also enhanced. Carbonization treatment is carried out within the temperature range of 700~1300℃, and a carbon material with a certain conductivity can be obtained, which is of great significance for its application in the fields of electrochemical energy storage, catalysis, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 It is a schematic diagram of the process of preparing a self-supporting thin film hard carbon material in the present invention; Figure 2 is a scanning electron microscope image (SEM) of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention; Figure 3 This is a constant current charge and discharge curve of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention as a negative electrode material in a sodium ion battery; Figure 4 is the rate curve of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention as a negative electrode material in a sodium ion battery; Figure 5 The cycle curve of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention as the negative electrode material in a sodium ion battery Figure 6 The cyclic voltammetry (CV) curve of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention as a negative electrode material in a sodium ion battery. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0029] like Figure 1 As shown, the present invention provides a method for preparing a self-supporting carbonized thin film material with a micron-level thickness, which specifically comprises the following steps: S1: dissolving p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride in N-methylpyrrolidone, and performing in-situ polymerization to obtain a polyamic acid solution; Specifically, p-phenylenediamine is added to N-methylpyrrolidone, ultrasonicated for 5 to 10 minutes, and then 3,3',4,4'-biphenyltetracarboxylic dianhydride is added in batches, and in-situ polymerization is performed in a water bath to obtain a polyamic acid solution, and the polyamic acid solution is defoamed in a vacuum oven to obtain a defoamed polyamic acid solution. The ratio of p-phenylenediamine to the N-methylpyrrolidone is 1 mol: (35 to 60) mL, and the molar ratio of p-phenylenediamine to 3,3',4,4'-biphenyltetracarboxylic dianhydride is (1 to 1.02): 1.
[0030] S2: using the polyamic acid solution to prepare a polyamic acid film, wherein the thickness of the polyamic acid film is in the micrometer order; the operation here may be to prepare a polyamic acid film with a micrometer thickness from the polyamic acid solution through a self-made coating machine and then put the film into a blast drying oven for drying to obtain a polyamic acid film material with a micrometer thickness; Specifically, the defoamed polyamic acid solution is poured onto a clean glass plate, the scraper of the coating machine is adjusted to a suitable thickness of 15-30 μm, and a polyamic acid film with a micron-level thickness is obtained by the coating machine; then the obtained polyamic acid film is placed in a blast drying oven for drying to obtain a polyamic acid film with a micron-level thickness, wherein the thickness of the dried polyamic acid film is 10-20 μm.
[0031] S3: performing imidization treatment on the polyamic acid film to obtain a polyimide film; the operation here may be placing the polyamic acid film material with a micron-level thickness in a blast drying oven and performing imidization treatment to obtain a polyimide film material with a micron-level thickness; Specifically, the micron-thick polyamic acid film material is placed in a blast drying oven for imidization treatment, and the temperature is increased in batches and kept warm for a period of time, wherein the imidization temperature is 100-350° C., and the insulation time at each temperature is 0.5-1 h.
[0032] S4: In an argon atmosphere, the polyimide film is carbonized to obtain the self-supporting film hard carbon material, and a pressure of 80 to 480 Pa is applied to the polyimide film during the carbonization treatment. Specifically, the micron-thick polyimide film is placed in a tubular furnace, argon is introduced to remove the air in the tube, and under the protection of the argon atmosphere, the tube furnace is used for high-temperature carbonization, the carbonization temperature is 700 to 1300°C, the time is 1 to 2 hours, and the heating rate can be 2°C / min, to obtain the self-supporting film hard carbon material.
[0033] In addition, the present invention also discloses a self-supporting thin film hard carbon material prepared by the above method, and also discloses a negative electrode material containing the above self-supporting thin film hard carbon material, and also discloses a sodium ion battery containing the above negative electrode material. The assembly steps of the sodium ion battery are: in a glove box filled with argon, the positive electrode shell, the sodium sheet positive electrode sheet, the glass fiber diaphragm, the electrolyte, the negative electrode sheet, and the negative electrode shell are stacked and sealed in sequence, and the electrolyte is NaCF3SO3 to complete the battery assembly.
[0034] The self-supporting thin film hard carbon material prepared by the preparation method of the present invention has typical hard carbon structure sodium storage behavior. Through the microstructure characterization and electrochemical sodium storage test of the electrode material, the present invention found that the micron-thick self-supporting carbonized thin film material obtained by calcining at 1300°C has a sodium storage capacity of 50 mA g -1 The first reversible specific capacity is 389 mAh g -1 The first coulombic efficiency is 81.4%. At a current density of 50 mA g -1 After 300 cycles, the specific capacity remains at 376 mAh g -1 The capacity retention rate is 95.3%, which has excellent electrochemical performance. The self-supporting thin film hard carbon material of the present invention is used as the negative electrode material of the sodium ion battery, wherein the sodium ion battery is 50mAg -1 After 200 cycles at a current density of 1.5 %, the capacity retention rate was 90%~96%, and the first coulombic efficiency was 60%~90%. After 500 cycles under this condition, the capacity retention rate was 80%~95%, and the first coulombic efficiency was 30%~90%.
[0035] The preparation method of the present invention adopts a simple method to synthesize a self-supporting thin film hard carbon material. The method has a simple reaction process, is environmentally friendly and low in cost. The material structure is regulated by a simple method, and the special molecular structure of the polyimide precursor is fully utilized by controlling the dosage of the drug, the temperature and other parameters, so as to achieve excellent sodium storage characteristics. The micron-thick self-supporting polyimide film material prepared by the preparation method of the present invention is subjected to heat treatment at different temperatures to prepare a micron-thick self-supporting carbonized thin film electrode material. Polyimide is selected as a carbon material precursor. The polyimide has rich O and N content. After carbonization treatment, defect sites are formed. The defect sites serve as active sites, which effectively make the material have excellent rate performance and first coulomb efficiency. In addition, even after carbonization treatment, a certain amount of oxygen and nitrogen still exist in the polyimide-derived carbon material. These residual oxygen and nitrogen can exist in the form of functional groups (such as hydroxyl, carboxyl, ketone, amide, etc.) to form active sites, further enhancing the electrochemical properties of the material. The present invention selects a suitable polymer as a carbonization precursor and coordinates the carbonization process to rationally optimize the microstructure of the carbonaceous electrode material, thereby providing a feasible strategy for sodium ion batteries with high rate performance and long life.
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] Example 1 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N,N-dimethylformamide and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-scale thick polyimide film material between two graphite plates and put it into a tubular furnace, apply a micro-pressure of 90Pa to the polyimide film material, and introduce argon gas to expel the air in the tube; under the protection of argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2℃ / min to 1300℃, and keep the temperature for 2h, then cool it down to 200℃ at 2℃ / min, and then cool it naturally to obtain a self-supporting thin film hard carbon material.
[0039] Figure 2 This is a digital photo of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention. It can be seen from the figure that the prepared self-supporting thin film hard carbon material has good self-supporting properties.
[0040] at the same time, Figure 3 The constant current charge-discharge curve of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention as a negative electrode material in a sodium ion battery. It can be seen that the self-supporting thin film hard carbon material prepared in Example 1 as a negative electrode material is 50 mA g -1 At a current density of 395.5 mAh g -1 The reversible specific capacity is 2.5W, and its first coulombic efficiency can reach 81.4%; the constant current charge-discharge curve has a voltage platform of 0.1V, which corresponds to the charge-discharge behavior of hard carbon materials as negative electrode materials in sodium ion batteries.
[0041] The rate performance test of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention as a negative electrode material in a sodium ion battery is shown in Figure 4 ,It can be seen from the figure that sodium ion batteries have good rate performance at different current densities.
[0042] Figure 5 The self-supporting thin film hard carbon material prepared in Example 1 of the present invention is used as a negative electrode material in a sodium ion battery cycle performance test. Figure 5 It can be seen that the sodium ion battery at 50 mA g -1 It has good capacity retention at a current density of 2.5 %.
[0043] Figure 6 The cyclic voltammetry curve of the self-supporting thin film hard carbon material prepared in Example 1 of the present invention used as a negative electrode material in a sodium ion battery is shown in FIG. Figure 6 A pair of redox peaks can be seen near 0.01 V in the CV curve, corresponding to the adsorption / desorption process of sodium ions in the self-supporting thin film hard carbon material; irreversible reduction peaks appear at around 0.32 V and 0.67 V, which is related to the irreversible decomposition of the electrolyte and the formation of the SEI film during the charge and discharge process.
[0044] Example 2 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material in a tubular furnace, apply a pressure of 480Pa to the polyimide film, and introduce argon gas to expel the air in the tube; under the protection of the argon atmosphere, use a tubular furnace for high-temperature carbonization, increase the temperature to 900°C at a rate of 2°C / min, keep the temperature for 2h, then cool down to 200°C at a rate of 2°C / min, and then cool naturally to obtain a self-supporting thin film hard carbon material.
[0045] Example 3 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material in a tubular furnace, apply a pressure of 90Pa to the polyimide film, and introduce argon gas to expel the air in the tube; under the protection of the argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2°C / min to 1100°C, and keep the temperature for 2h, then cool it down to 200°C at 2°C / min, and then cool it naturally to obtain a self-supporting thin film hard carbon material.
[0046] Example 4 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material in a tubular furnace, apply a pressure of 200Pa to the polyimide film, and introduce argon gas to expel the air in the tube; under the protection of the argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2°C / min to 1300°C, and keep the temperature for 2h, then cool it down to 200°C at 2°C / min, and then cool it naturally to obtain a self-supporting thin film hard carbon material.
[0047] Example 5 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material in a tubular furnace, apply a pressure of 350Pa to the polyimide film, and introduce argon gas to expel the air in the tube; under the protection of the argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2°C / min to 1400°C, and a continuous temperature of 2h, then cool down to 200°C at 2°C / min, and then cool naturally to obtain a self-supporting thin film hard carbon material.
[0048] Example 6 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material between two graphite plates, apply a pressure of 400Pa to the polyimide film, and put it into a tubular furnace, and introduce argon gas to expel the air in the tube; under the protection of argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2°C / min to 900°C, and keep the temperature for 2h, then cool it to 200°C at 2°C / min, and then cool it naturally to obtain a self-supporting thin film hard carbon material.
[0049] Example 7 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material between two graphite plates, apply a pressure of 450Pa to the polyimide film, and put it into a tubular furnace, and introduce argon gas to expel the air in the tube; under the protection of argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2°C / min to 1100°C, and keep the temperature for 2h, then cool it to 200°C at 2°C / min, and then cool it naturally to obtain a self-supporting thin film hard carbon material.
[0050] Example 8 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: Step 1: Add 38 mL of N-methylpyrrolidone and p-phenylenediamine into a three-necked flask, ultrasonicate for 5 minutes to obtain a uniform solution, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches until the molar ratio reaches 1:1.02 to obtain a polyamic acid solution, and place the solution in a vacuum oven for defoaming; Step 2: pouring the defoamed polyamic acid solution onto a glass plate, adjusting the size of a scraper, and using a scraping machine to obtain a polyamic acid film with a micron-level thickness, and placing the obtained polyamic acid film with a micron-level thickness into a blast drying oven for drying to volatilize the residual organic solvent; Step 3: placing the obtained micron-sized polyamic acid film in a blast drying oven for imidization treatment, heating up and keeping the temperature for a period of time in batches, with a heating rate of 2°C / min, keeping the temperature at 100°C for 1h, keeping the temperature at 200°C for 1h, keeping the temperature at 300°C for 1h, and keeping the temperature at 350°C for 0.5h; then cooling naturally to obtain a micron-sized polyimide film material; Step 4: Place the obtained micron-level thick polyimide film material between two graphite plates, apply a pressure of 480Pa to the polyimide film, put it into a tubular furnace, and introduce argon gas to expel the air in the tube; under the protection of argon atmosphere, use a tubular furnace for high-temperature carbonization, with a heating rate of 2°C / min to 1400°C, and keep the temperature for 2h, then cool it down to 200°C at 2°C / min, and then cool it naturally to obtain a self-supporting thin film hard carbon material.
[0051] Example 9 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: S1: Add p-phenylenediamine to N-methylpyrrolidone, perform ultrasonic treatment for 5 minutes, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches, perform in-situ polymerization in a water bath, obtain a polyamic acid solution, and defoam the polyamic acid solution in a vacuum oven to obtain a defoamed polyamic acid solution. The ratio of p-phenylenediamine to N-methylpyrrolidone is 1 mol:35 mL, and the molar ratio of p-phenylenediamine to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 1:1.
[0052] S2: Pour the defoamed polyamic acid solution onto a clean glass plate, adjust the scraper of the coating machine to a suitable thickness of 15 μm, and obtain a polyamic acid film with a micron-level thickness through the coating machine; then put the obtained polyamic acid film into a blast drying oven for drying to obtain a polyamic acid film with a micron-level thickness, wherein the thickness of the dried polyamic acid film is 10 μm.
[0053] S3: placing the micron-thick polyamic acid film material into a blast drying oven for imidization treatment, heating it in batches and keeping it warm for a period of time, wherein the imidization temperature is 100° C., 200° C., 300° C., and 350° C., and the insulation time at each temperature is 0.5 h.
[0054] S4: In an argon atmosphere, the polyimide film is subjected to a carbonization treatment to obtain the self-supporting film hard carbon material. During the carbonization treatment, a pressure of 80 Pa is applied to the polyimide film. The carbonization treatment temperature is 700° C., the time is 2 h, and the heating rate can be 2° C. / min to obtain the self-supporting film hard carbon material.
[0055] The sodium ion battery assembled with the negative electrode material made of the self-supporting thin film hard carbon material has a high performance at 50 mA g -1 After 200 cycles at a current density of , the capacity retention rate is 90% and the first coulombic efficiency is 60%.
[0056] Example 10 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: S1: Add p-phenylenediamine to N-methylpyrrolidone, perform ultrasound for 10 minutes, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches, perform in-situ polymerization in a water bath, obtain a polyamic acid solution, and defoam the polyamic acid solution in a vacuum oven to obtain a defoamed polyamic acid solution. The ratio of p-phenylenediamine to the N-methylpyrrolidone is 1 mol:60 mL, and the molar ratio of p-phenylenediamine to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 1.02:1.
[0057] S2: Pour the defoamed polyamic acid solution onto a clean glass plate, adjust the scraper of the coating machine to a suitable thickness of 30 μm, and obtain a polyamic acid film with a micron-level thickness through the coating machine; then put the obtained polyamic acid film into a blast drying oven for drying to obtain a polyamic acid film with a micron-level thickness, wherein the thickness of the dried polyamic acid film is 20 μm.
[0058] S3: placing the micron-thick polyamic acid film material into a blast drying oven for imidization treatment, heating it in batches and keeping it warm for a period of time, wherein the imidization temperature is 100° C., 200° C., 300° C., and 350° C., and the insulation time at each temperature is 1 hour.
[0059] S4: In an argon atmosphere, the polyimide film is subjected to a carbonization treatment to obtain the self-supporting film hard carbon material. During the carbonization treatment, a pressure of 480 Pa is applied to the polyimide film. The temperature of the carbonization treatment is 1300° C., the time is 1 hour, and the heating rate can be 2° C. / min to obtain the self-supporting film hard carbon material.
[0060] The sodium ion battery assembled with the negative electrode material made of the self-supporting thin film hard carbon material has a high performance at 50 mA g -1 After 200 cycles at a current density of , the capacity retention rate was 96% and the first coulombic efficiency was 90%.
[0061] Embodiment 11 A method for preparing a self-supporting thin film hard carbon material comprises the following steps: S1: Add p-phenylenediamine to N-methylpyrrolidone, perform ultrasonic treatment for 8 minutes, then add 3,3',4,4'-biphenyltetracarboxylic dianhydride in batches, perform in-situ polymerization in a water bath, obtain a polyamic acid solution, and defoam the polyamic acid solution in a vacuum oven to obtain a defoamed polyamic acid solution. The ratio of p-phenylenediamine to N-methylpyrrolidone is 1 mol:50 mL, and the molar ratio of p-phenylenediamine to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 1:1.
[0062] S2: Pour the defoamed polyamic acid solution onto a clean glass plate, adjust the scraper of the coating machine to a suitable thickness of 20 μm, and obtain a polyamic acid film with a micron-level thickness through the coating machine; then put the obtained polyamic acid film into a blast drying oven for drying to obtain a polyamic acid film with a micron-level thickness, wherein the thickness of the dried polyamic acid film is 14 μm.
[0063] S3: placing the micron-thick polyamic acid film material into a blast drying oven for imidization treatment, heating it in batches and keeping it warm for a period of time, wherein the imidization temperature is 100° C., 200° C., 300° C., and 350° C., and the insulation time at each temperature is 0.8 h.
[0064] S4: In an argon atmosphere, the polyimide film is subjected to a carbonization treatment to obtain the self-supporting film hard carbon material. During the carbonization treatment, a pressure of 450 Pa is applied to the polyimide film. The carbonization temperature is 1000° C., the time is 1.5 h, and the heating rate can be 2° C. / min to obtain the self-supporting film hard carbon material.
[0065] The sodium ion battery assembled with the negative electrode material made of the self-supporting thin film hard carbon material has a high performance at 50 mA g -1 After 200 cycles at a current density of , the capacity retention rate was 92% and the first coulombic efficiency was 80%.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a self-supporting thin film hard carbon material, characterized in that: The following steps are involved: S1: dissolving p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride in N-methylpyrrolidone, and performing in-situ polymerization to obtain a polyamic acid solution; S2: preparing a polyamic acid film using the polyamic acid solution, wherein the thickness of the polyamic acid film is in the micrometer level; S3: performing imidization treatment on the polyamic acid film to obtain a polyimide film; S4: Under an argon atmosphere, the polyimide film is carbonized to obtain the self-supporting film hard carbon material. During the carbonization, a pressure of 80-480 Pa is applied to the polyimide film.
2. The method for preparing a self-supporting thin film hard carbon material according to claim 1, characterized in that: In step S1, p-phenylenediamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride are dissolved in N-methylpyrrolidone, specifically: p-phenylenediamine is dissolved in N-methylpyrrolidone, and after ultrasonic treatment, 3,3',4,4'-biphenyltetracarboxylic dianhydride is added in batches, and stirred evenly to obtain the polyamic acid solution; the ratio of the p-phenylenediamine to the N-methylpyrrolidone is 1 mol: (35~60) mL.
3. The method for preparing a self-supporting thin film hard carbon material according to claim 1, characterized in that: In step S1, the molar ratio of the p-phenylenediamine to the 3,3',4,4'-biphenyltetracarboxylic dianhydride is (1-1.02):
1.
4. The method for preparing a self-supporting thin film hard carbon material according to claim 1, characterized in that: In step S2, the thickness of the polyamic acid film is 10-20 μm.
5. The method for preparing a self-supporting thin film hard carbon material according to claim 1, characterized in that: In step S3, the imidization treatment is specifically: performing a gradient temperature treatment within a range of 100 to 350° C., and the treatment time at each temperature is 0.5 to 1 h.
6. The method for preparing a self-supporting thin film hard carbon material according to claim 5, characterized in that: During the gradient temperature increase treatment, the temperature increase rate is 2-5°C / min.
7. The method for preparing a self-supporting thin film hard carbon material according to claim 1, characterized in that: In step S4, the temperature of the carbonization treatment is 700-1300° C., and the time is 1-2 hours.
8. A self-supporting thin film hard carbon material, characterized in that: Prepared by the method according to any one of claims 1 to 8.
9. A negative electrode material, characterized in that: The self-supporting thin film hard carbon material according to claim 8 is included.
10. A sodium ion battery, characterized in that: The negative electrode material according to claim 9 is included, wherein the sodium ion battery has an output current of 50 mA g -1 After 200 cycles at a current density of 1.547 W, the capacity retention rate is 90%~96%, and the first coulombic efficiency is 60%~90%.
Citation Information
Patent Citations
Preparation method for polyimide thin film
CN105237785A
Carbon film and process for preparing the same
US5352524A
